From Ecolinguistics to Environmental Linguistics: Towards a Cognitive–Ecological Model of Language and Sustainability - Yayouche, Djaafar (Journal of Ecohumanism, 2025)
This study develops a comprehensive Cognitive–Ecological Framework that redefines the transition from Ecolinguistics to Environmental Linguistics through an epistemological and ecological reorientation. Revisiting Saussure’s internal–external dichotomy, it constructs an “Archaeological Bridge” connecting structural linguistics with cognitive–ecological paradigms, while introducing an Arab contribution grounded in cognitive semiotics and environmental ethics. A triangulated mixed-methods design integrates discourse, cognitive, and ecological analyses. The applied dimension employs EEG, Eye-Tracking, and Olfactory–Tactile stimuli, supported by computational modeling (TF–IDF and regression analysis), to examine how language activates sensory and ecological cognition in Arabic sacred and literary discourse. Empirical findings reveal measurable sensory engagement in Arabic literary and Qur’ānic texts. Qur’ānic discourse, in particular, enhances visual and auditory processing by +37% and +28%, respectively, demonstrating the text’s neuro-cognitive capacity to transform aesthetic and ethical perception into ecological awareness. Findings confirm that Ecolinguistics can evolve from a descriptive discourse discipline into a predictive, measurable science of environmental cognition. The proposed “Saussurean Environmental Turn” positions language as both symbolic and ecological, bridging linguistics, neuroscience, and sustainability. By uniting epistemological depth with experimental precision, the Cognitive–Ecological Model establishes an original Arab–Qur’ānic contribution to global ecolinguistics, showing how sacred and literary texts function as neuro-cognitive systems that foster environmental ethics and sustainable awareness.